Caveolin-1 and CDC42 mediated endocytosis of silica-coated iron oxide nanoparticles in HeLa cells - Bohmer, Nils; Jordan, Andreas (Beilstein Journal of Nanotechnology, 2015)
Nanomedicine is a rapidly growing field in nanotechnology, which has great potential in the development of new therapies for numerous diseases. For example iron oxide nanoparticles are in clinical use already in the thermotherapy of brain cancer. Although it has been shown, that tumor cells take up these particles in vitro, little is known about the internalization routes. Understanding of the underlying uptake mechanisms would be very useful for faster and precise development of nanoparticles for clinical applications. This study aims at the identification of key proteins, which are crucial for the active uptake of iron oxide nanoparticles by HeLa cells (human cervical cancer) as a model cell line. Cells were transfected with specific siRNAs against Caveolin-1, Dynamin 2, Flotillin-1, Clathrin, PIP5Kα and CDC42. Knockdown of Caveolin-1 reduces endocytosis of superparamagnetic iron oxide nanoparticles (SPIONs) and silica-coated iron oxide nanoparticles (SCIONs) between 23 and 41%, depending on the surface characteristics of the nanoparticles and the experimental design. Knockdown of CDC42 showed a 46% decrease of the internalization of PEGylated SPIONs within 24 h incubation time. Knockdown of Dynamin 2, Flotillin-1, Clathrin and PIP5Kα caused no or only minor effects. Hence endocytosis in HeLa cells of iron oxide nanoparticles, used in this study, is mainly mediated by Caveolin-1 and CDC42. It is shown here for the first time, which proteins of the endocytotic pathway mediate the endocytosis of silica-coated iron oxide nanoparticles in HeLa cells in vitro. In future studies more experiments should be carried out with different cell lines and other well-defined nanoparticle species to elucidate possible general principles.
Keywords: Caveolin-1; CDC42; endocytosis inhibition; iron oxide nanoparticles; nanoparticle uptake